Nutrient Composition of Eel Anguilla bicolor bicolor and Anguilla marmorata - Ikromatun Nafsiyah; Mala Nurilmala; Asadatun Abdullah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2018)
Eel (Anguilla sp.) is a highly nutritious Indonesian marine commodity. However, information on the eel nutrient content in Indonesia is still limited. This study was aimed to determine chemical properties of Indonesian eels,Anguilla bicolor bicolor and A. marmorata. Proximate, amino acid, fatty acid, and vitamin A analysis were carried out on the fresh eel. The A. bicolor bicolor  ontained 65.51% of moisture, 1.34% of ash, 16.78% of protein, 13.26% of fat, and 3.1% of carbohydrate. Meanwhile, results on A. marmorata showed it contained 57.17% of moisture, 1.09% of ash, 17.30% of protein, 21.35% of fat, and 3.12% of carbohydrate. Leucine and glutamic acid represented the highest essential and non-essential amino acid of both A. bicolor bicolor and A. marmorata, respectively. The highest saturated and monounsaturated fatty acid were palmitate and oleic acid for A. bicolor bicolor as well as A. marmorata. The content of vitamins in A. marmorata was higher than in A. bicolor bicolor.